Socio-academic factors associated with academic performance in university students - Lucendo, Manuel Cañas; Herrera, Yosbanys Roque; Reyna, Mónica Alexandra Castelo; Gaibor, Gustavo Javier Ávila (International Journal of Innovative Research and Scientific Studies, 2025)
Academic performance (AP) is an important dimension in the educational field and can be affected by the incidence of various socio-academic factors. Purpose: This research aimed to analyze AP considering factors such as major, term, and socioeconomic level in students of the Faculty of Health Sciences of the National University of Chimborazo in Riobamba, Ecuador, during the second academic period in 2021. Methodology: The study had a quantitative approach, non-experimental design, and cross-sectional analytical scope. The population consisted of 1,146 students enrolled in the courses of that university environment. The data collected from the individual files were processed using a binary regression model and other comparison and correlation models. Findings: Academic performance classified as regular prevailed in nine of the educational levels included; its relative frequencies ranged between 39.67% and 56.86%. There was a statistically significant dependence between academic performance and the term that the participants were studying (X2=115.80; p=0.00) and the race (X2=142.82; p=0.00). Conclusion: Major constituted a factor with predictive value concerning AP. Medicine students were more likely to score more than 6.99 points than those enrolled in Dentistry.